Essential polyunsaturated fatty acid and lipid peroxide levels in never-medicated and medicated schizophrenia patients - Arvindakshan, Meena; Sitasawad, Sandhya; Debsikdar, Vijay; Ghate, Madhav; Evans, Denise; Horrobin, David F; Bennett, Crispin; Ranjekar, Prabhakar K; Mahadik, Sahebarao P (Biological psychiatry (1969), 2003)
Reduced levels of membrane essential polyunsaturated fatty acids (EPUFAs) and increased levels of lipid peroxidation products (thiobarbituric acid reactive substances; TBARS) have been observed in chronic medicated schizophrenics. The relationship of EPUFA and TBARS to psychopathology is unclear, since their levels may be altered differentially by duration of illness and antipsychotic treatment. To minimize these confounds, their levels were compared among never-medicated patients in early illness, medicated patients and control subjects with similar lifestyle and common ethnic background. RBC membrane EPUFAs, plasma TBARS, and various dimensions of psychopathology were measured using established procedures in never-medicated ( n = 20) and medicated ( n= 32) schizophrenia patients and in control subjects ( n= 45). Reduced levels of EPUFAs, particularly arachidonic acid (AA) and docosahexaenoic acid (DHA), were found in never-medicated compared with control subjects; however, the reductions in levels of both AA and DHA were much smaller in medicated versus never-medicated patients; AA levels were similar to levels in control subjects. Only DHA levels were significantly reduced in medicated patients. Lower membrane AA levels were associated with increased levels of plasma TBARS in never-medicated patients. Lower levels of membrane EPUFAs and higher levels of plasma TBARS were associated with the severe symptoms in never-medicated versus medicated patients. Data indicate that reduced EPUFAs and increased TBARS exist in never-medicated patients, and these measures correlate with the severity of psychopathology indicating that the membrane EPUFA status may reflect the outcome of schizophrenia.